Tellurium Chemistry in Brazil: Origin and Development - Princival, Cleverson; F. Z. J. Amaral, Mônica; A. Dos Santos, Alcindo; V. Comasseto, Joao (Current Organic Synthesis, 2015)
This article gives a historical background on the introduction of the chalcogen chemistry in Brazil. It also describes the development of synthetic methods based on organotellurium compounds, and their use in the synthesis of biologically active compounds. A brief comment on the biological activity of organotellurium compounds is also made.
Keywords: organic synthesis